Relative efficiency of plantation companies in Malaysia: a financial ratio-based data envelopment analysis approach - Abdul Wahab, Abdul Hamid; Abdul Razak, Dzuljastri (2015)
This study examines the relative efficiency of 31 plantation companies in Malaysia based on data for the first three cummulated quarters of 2012 (January - September). The study applies an adopted version of Data Envelopment Analysis (DEA). DEA is a tool used to weigh the inputs/outputs and measure the relative efficiency of decision-making units. This research adopts an output-oriented form of DEA based on financial ratios without the utilization of inputs. The innovative adopted DEA model provides a comprehensive decision on a company’s efficiency by taking into account various financial ratios all together and combining them into a single measure of efficiency. The results show that out of the 31 plantation companies in Malaysia, only five (16.13%) proved to be efficient. Also, it is found that the higher a company’s financial ratio in relation to the equivalent ratios of other companies, the higher the efficiency score of that company. Keywords: Efficiency, Data Envelopment Analysis, Malaysia, Plantation Companies